Natural organic matter in water characterization, treatment methods, and climate change impact. - Sillanpaa, Mika E. T.; Park, Yuri (Butterworth-Heinemann, 2023)
Natural Organic Matter in Water: Characterization, Treatment Methods, and Climate Change Impact, Second Edition focuses on advanced filtration and treatment options, as well as processes for reducing disinfection by-products, making it an essential resource on the latest breakthroughs in the characterization, treatment and removal of natural organic matter (NOM) from drinking water. Based on the editor's years of research and field experience, the book covers general parameters, isolation and concentration, fractionation, composition and structural analysis, and biological testing, along with removal methods such as inorganic coagulants, polyelectrolytes and composite coagulants. In addition, sections cover electrochemical and membranes removal methods such as electrocoagulation, electrochemical oxidation, microfiltration and ultrafiltration, nanofiltration, and membrane fouling. This book is a valuable guide for engineers and researchers looking to integrate methods, processes and technologies to achieve desired affects.